Treatment of Cervical Discal Hernia with Ozone under Fluroscopic Navigation (Ozone Therapy Global Journal, 2018)
The purpose of the present prospective study was to demonstrate that cervical percutaneous discolysis with ozone therapy is effective and safe for cervical segment hernia treatments that cause pain.A total of 115 percutaneous discolysis was performed with O2-O3 in patients with severe neck pain, during a period between May 2012 and May 2016. All discolysis were performed under fluoroscopic guidance under strict aseptic and antisepsis measures and local anesthesia. Patients were given an ozone volume of (3-5) mL at a concentration of 10μg/mL. In all cases, 1 g of Cefacidal® (Cefazolin Sodium) was administered as prophylaxis. The evolution, according to the visual analogue scale showed that the improvement with respect to the initial state was significant (p